Religion and Social Change: Main Directions of Mutual Influence - Ganbarov, Asaf (Scholarya Demo Journal of Ruby, 2020)
This article deals with the study of the mutual influence between religion and social change from a sociological point of view. The topic of religion and social change, as one of the actual problems of the sociology of religion, has attracted the attention of social scientists and various works have appeared in this field. The purpose of this study is to review researches on the relationship between religion and social change and to analyze objectively the topic on the basis of sociological theories and historical facts. The article, first of all, explains the concept of social change in sociological thought. It is noted that social change is not a temporary and formal change, but a permanent change in the socio-cultural system. The interaction of religion with such system changes is multifaceted and complex. The author analyzes the relationship between religion and social change from three aspects: religion as an obstacle to social change, religion as a cause of social change and the impact of social change on religion. First of all, it has been concluded that religion can rarely interfere with social change, but this is usually due to the activities of an organized clergy. Thus, the founders of religion and reformists are usually trying to implement changes and innovations. The topic of religion as a cause of social change is also an important issue. In this regard, the author gives various examples of how religion promotes social change on the basis of concrete historical facts. In respect of the impact of social change on religion, it is noted that due to legal, political, socio-cultural changes in society, it is undeniable that various changes and reforms have taken place in both the organizational structure and doctrines of religions.